Production of biosurfactant by Bacillus subtilis UCP 0999 using cassava wastewater (CWW) and waste frying oil (WFO) as renewable substrates (Research, Society and Development, 2022)
This study focused on the low-cost production of biosurfactant by Bacillus subtilis UCP 0999, using cassava wastewater (CWW) and waste frying oil (WFO) as renewable substrates. A 22 full-factorial design (FFD) was employed to investigate the effects of concentrations of agro-industrial wastes in surface tension (ST) and emulsification index (EI24). According to the results, the minimum value of ST (33.2 mN/m) and the maximum value of EI24 (95%) was obtained at central point of the FFD, using 5% CWW and 2% WFO. Statistical analyses demonstrated the significative influence of both substrates in ST and EI24. The biosurfactant showed 2.67 g/L yield and anionic and lipopeptide nature by Zeta potential and Fourier transform infrared (FT-IR) spectroscopy, respectively. In addition, promising applications of biosurfactant as biodispersant and viscosity reducing agent were demonstrated, suggesting its potential use in petroleum industry or bioremediation of hydrophobic pollutants.